Study of Drivers’ Behaviour at a Passive Railway Crossing - Sandra Kasalica; Radisav Vukadinović; Vojkan Lučanin (Promet (Zagreb), 2012)
Problem: The number of killed and injured persons in incidents at railway level crossings is generally increasing on the Serbian Railways, particularly at passive crossings. In this paper we researched the direct behaviour of road traffic participants at a conventional railway passive crossing. Method: Direct observational study of drivers’ behaviour at a level crossing. Results: Sixty-one road vehicle drivers were observed in the moments of train approach. The probability of crossing varies depending on the train distance and the time the driver has to cross the crossing. The drivers who have limited visibility cannot estimate the speed of the approaching train well and make more risky decisions. Conclusion: This study shows that the number of “risky crossings” is worrying as the result of such crossings is a large number of accidents with fatal consequences at the passive crossings in Serbia.